THE EFFECT OF PLACENTAL ABRUPTION ON PREGNANCY OUTCOME - Babic, Sandra; Jovandarić, Miljana (Srpski medicinski časopis Lekarske komore, 2022)
Placental abruption is defined as the premature separation of the placenta from the uterus. Rapid diagnosis and adequate medical intervention provide a good outcome, which is not possible in all countries. Any bleeding that occurs in the second half of pregnancy raises the suspicion of placental abruption, which is associated with fetal and maternal morbidity and mortality. The clinical picture and consequences for the fetus depend on the degree of bleeding and the amount of blood. Complete abruption leads to the disruption of fetal circulation and oxygenation, asphyxia, and stillbirth. In case of partial abruption, the consequences for the fetus depend on the degree of bleeding. In complete abruption, fetal death is inevitable unless an emergency cesarean delivery is undertaken.